ASPECTS OF LEGAL CERTAINTY REGARDING THE TRANSFER OF LAND RIGHTS USING A POWER OF ATTORNEY DEED - Khairunnisah, Khairunnisah (PT. Altin Riset Publishing, 2024)
This study aims to examine the legal certainty in the mechanism of transferring land rights through a deed of authority to sell, by integrating philosophical, juridical, and sociological perspectives. Philosophically, legal certainty is seen as the embodiment of justice and moral values that require every legal instrument, including the power to sell, to be based on the principles of legality and justice in order to create a harmonious social order. The juridical approach emphasizes that the use of the power to sell must fulfill formal and material requirements under the Basic Agrarian Law and its derivative regulations. In this case, the role of the Notary or PPAT (a government official) as the authorized official is key in realizing the legal force and certainty of the status of land rights. This research uses an empirical juridical method with a legal analysis approach. Data was collected through observation and interviews to verify the procedure for making deeds, the mechanisms of administrative and taxation verification, and the role of authorized officials. The results showed that the validity of the power of attorney to sell depends heavily on administrative completeness, such as clearly stating the identities of the parties, the object, and the power of attorney clause. A systematic and transparent deed-making procedure, conducted by a notary or land official, has been proven to minimize potential disputes. Administrative verification integrated with tax compliance further strengthens the legitimacy of transactions. Thus, a deed of power of attorney to sell made by statutory regulations can increase legal certainty and legal protection for the parties, especially for bona fide buyers.